Framtidens sjömän - Skapas intresset i skolan? - Green, Marcus (My University, 2014)
The purpose of this study is to find out if the S/Y Älva is vital to get future high school students to apply for Marina läroverket (ML), and of their studys on ML has influence on their future choice of profession. Hopefully the results can be used to develop the school's future recruitment and marketing. The study is conducted with the hope that the results from ML together with results from a similar study on Öckerö high school will demonstrate the importance of schools to create maritime interest in the young. The survey is conducted with the method, case study, which will include two parts. The first stage is carried out by means of a questionnaire distributed to one class in each program and grade. The second part consists of follow-up telephone interviews with selected students six years after the questionnaire survey was conducted. The results of the questionnaire study shows a number of different factors that motivated the students to apply for ML. On the Natural Resources/science program (MB) the science competence was the main factor. In the social science program (LK) the leadership and communication orientation was the most important. The automotive program (MT) students said that the vocationally-oriented program with good job opportunities after graduation attracted most. The interviews revealed that the high school has a large impact on the students. The marine orientation was not crucial to create a maritime interest. Some had an increased interest in shipping and maritime professions, others lost the interest they had. For those who chosed a career in shipping, you cant´ prove that the schools' marine orientation or their sailing ships expeditions was crucial. For those who lost their interest it was mostly the sailing ship expeditions and the special life at sea that gave them the insight.
Keywords: Transport; Annan teknik; Transport; Other Engineering and Technologies